FREQUENCY AND PREVENTION OF LAPAROSCOPIC PORT SITE INFECTION - Taj, Muhammad Naeem; Iqbal, Yasmeen; Akbar, Zakia (Journal of Ayub Medical College Abbottabad, 2012)
Background: The present study was conducted to evaluate the usefulness and safety of the nonpowder surgical glove for extraction of the gallbladder in laparoscopic cholecystectomy. Methods: The study was carried out in Capital Hospital Islamabad and in a private hospital. The duration of study was from March 2009 to March 2012. This was an observational study carried out in 492 patients who underwent laparoscopic cholecystectomy using the surgical glove for extraction of the gallbladder and compared with the conventional method of gall bladder removal in two hospitals were analyzed. The operative findings, port site infection and co morbid conditions were evaluated. Results: Postoperative wound infection was found in 27 (5.48%) of 492 cases. Umbilical port infection was found in 26 (5.28%) of cases in which gall bladder was removed without endogloves and only one case (0.2%) had infection when gall bladder was removed with the endogloves. Wound infection was more in acute cholecystitis (25.9%) and empyema of Gall Bladder (44.4%). Among the co morbid conditions, diabetes mellitus has got higher frequency of wound infection (44%). Conclusion: The use of the surgical glove for extraction of the gallbladder is safe, cheap, simple and potentially reduces significant morbidity. Its routine use at laparoscopic cholecystectomy is mandatory in all cases. Keyword: laparoscopic cholecystectomy; non-powder surgical gloves; retrieval bag; wound infection